2009
DOI: 10.1590/s1678-91992009000200013
|View full text |Cite
|
Sign up to set email alerts
|

ALT-C, a disintegrin-like Cys-rich protein from Bothrops alternatus, increases skeletal myoblast viability

Abstract: ALT-C, an ECD motif (glutamic acid, cysteine, aspartic acid) disintegrin from Bothrops alternatus snake venom, induces α2β1 integrin-mediated signaling and neutrophil chemotaxis. In vitro, in human umbilical vein endothelial cells (HUVEC), ALT-C induces cell proliferation, thus showing an interesting potential for tissue regeneration studies. This work aimed to evaluate the influence of ALT-C in myoblast viability and differentiation. Myoblasts were obtained from hind limb muscles of 3 to 4-day old Wistar rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The venom increased the viability of HeLa cells at lower doses (1.25 and 2.5 μg/ml). This effect can be observed for snake venoms and also scorpion venoms because of proteins, peptides and other organic compounds that may promote cell proliferation at lower concentrations (Mesquita-Ferrari et al 2009;Erdeş et al 2014;Yalcin et al 2014). According to the results, HeLa (IC 50 = 12.80 μg/ml) is the most resistant cell line against all venom doses, while Vero and U-87 MG cell lines seem to be the most sensitive of the tested cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…The venom increased the viability of HeLa cells at lower doses (1.25 and 2.5 μg/ml). This effect can be observed for snake venoms and also scorpion venoms because of proteins, peptides and other organic compounds that may promote cell proliferation at lower concentrations (Mesquita-Ferrari et al 2009;Erdeş et al 2014;Yalcin et al 2014). According to the results, HeLa (IC 50 = 12.80 μg/ml) is the most resistant cell line against all venom doses, while Vero and U-87 MG cell lines seem to be the most sensitive of the tested cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…Previously results from our group have shown that ALT‐C strongly induces human vein endothelial cell (HUVEC) proliferation both in vitro and in vivo by up‐regulating the expression of some growth factors and their receptors, including vascular endothelial growth factor (VEGF) and VEGF receptor 2 (VEGFR‐2) (18,19). In addition, it was shown that ALT‐C increases myoblast proliferation, modifies gene expression including the pattern of MHC gene expression (20) and modulates matrix metalloprotease (MMP) activity and expression in an in vivo skeletal muscle regeneration model (21).…”
Section: Introductionmentioning
confidence: 99%
“…Due to frequent venom collection, inflammatory diseases in snake venom glands often occur and the pathogens are usually identified as bacteria. Although purification and gene expression of snake venom components have been extensively studied, there is no report on lipocalin homologue in snake venom glands (18)(19)(20)(21). Herein, the molecular cloning of a fulllength cDNA encoding a lipocalin homologue (d-lipo) in Deinagkistrodon acutus venom gland is reported, as well as the phylogenetic relationships among d-lipo and known homologues from other species.…”
Section: Introductionmentioning
confidence: 99%